Essays on smartphones' effects on attention and behavior - Kristoffer Lind Glavind (University of Copenhagen, Department of Economics, 2021)
Since the introduction of the iPhone in 2007, smartphones have become an integrated part of human life. Smartphones are excellent tools that help us access information, coordinate journeys, connect with friends and family, and much, much more. However, in parallel with the proliferation of smartphones, more and more concerns about adverse effects on human life have been raised. Research has shown that smartphones can be addictive, affect cognitive abilities, negatively influence social and intimate relationships, reduce academic performance, and correlate with depression and low well-being. In this Ph.D. dissertation, I analyze how smartphones affect human life through three separate chapters. Though examining different domains of human life, the chapters have several things in common. First, they all relate to how smartphones affect human attention. Second, they all use data collected from smartphones to examine the influence of smartphones. Third, in all three chapters, analyzes are made based on advanced data structuring and the use of econometric models seeking to establish causal claims when possible.
Keywords: 330